A tale of two cities - Dickens, Charles (New York : Bantam Books, 1989)
Relates the adventures of a young Englishman who gives his life during French Revolution to save the husband of the woman he loves
Keywords: London (England) -- History -- 18th century -- Fiction; Paris (France) -- History -- 1789-1799 -- Fiction; France -- History -- Revolution. 1789-1799 -- Fiction